Strategi Perencanaan Paket Wisata Gwk Sebagai Main Destination - Nugraha, Rizki Nurul; Khaeriyah, Khaeriyah; Wulan, Wulan (Jurnal Ilmiah Wahana Pendidikan, 2023)
Travel is done to relax yourself after the saturation of daily activities. To make it easier for tourists who want to take a vacation without the headache of taking care of everything, they can use the services of travel agents who have prepared tour packages according to their goals. Therefore, this research discusses "GWK Tour Package Planning Strategy as Main Destination". The tour package planning was made by "YangSeru Tours and Travel" which is a professional travel agent. The tour to GWK was conducted on August 22, 2022. The tour package is very helpful in the process of booking entrance tickets, show tickets and travel transportation. This journal aims to analyze the planning strategy of Garuda Wisnu Kencana (GWK) tour package as the main destination by YangSeru Tours and Travel company using SWOC (Strengths, Weaknesses, Opportunities, and Challenges) method. Through this case study, the author analyzes the identification of tour package planning strategies, the implementation of these strategies, as well as the impact of GWK tour package planning strategies. This research provides important insights for the tourism industry in Indonesia in developing effective tour package planning strategies to promote GWK as a major destination.